A pragmatic assessment of contextual fit and feasibility for e-learning implementation among public health workers in 16 West African countries: a mixed-methods study - Kehinde O. Ogunyemi; Virgil K. Lokossou; Lionel S. Sogbossi; Chima Ohuabunwo; Simon Antara; Senait Kebede; Carol Haley; Tolbert Nyenswah; Melchior A. Aïssi; Scott McNabb (Journal of Global Health Economics and Policy)
# Background E-learning plays a key role in bridging competency gaps among the public health workforce to prevent, detect, and respond to public health emergencies. However, its implementation remains a challenge in resource-limited settings. In this study, we assessed the contextual fit and feasibility of a multi-communication online training (MOT) for its effective implementation.